2017
DOI: 10.1111/papr.12609
|View full text |Cite
|
Sign up to set email alerts
|

Methadone versus Fentanyl in Patients with Radiation‐Induced Nociceptive Pain with Head and Neck Cancer: A Randomized Controlled Noninferiority Trial

Abstract: This is the first study to show noninferiority of methadone compared to fentanyl at 1 and 3 weeks in the treatment of radiation-induced nociceptive pain in patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In a randomized controlled trial of 52 patients, Haumann et al demonstrated that methadone was superior to fentanyl for neuropathic pain due to HNC . A subsequent randomized controlled trial of 82 patients demonstrated the noninferiority of methadone to fentanyl specifically for patients with HNC experiencing radiation‐induced pain; the authors also found less need to escalate opioids with the use of methadone …”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled trial of 52 patients, Haumann et al demonstrated that methadone was superior to fentanyl for neuropathic pain due to HNC . A subsequent randomized controlled trial of 82 patients demonstrated the noninferiority of methadone to fentanyl specifically for patients with HNC experiencing radiation‐induced pain; the authors also found less need to escalate opioids with the use of methadone …”
Section: Discussionmentioning
confidence: 99%
“…Haumann et al ran two RCTs to compare the use of methadone to fentanyl in both nociceptive and neuropathic pain domains in OM. Opioidnaïve patients reported significantly decreased average pain with the use of methadone at 3 weeks of treatment (29).…”
Section: Discussionmentioning
confidence: 98%
“…Methadone may be more effective for neuropathic pain and unlike other opiates, methadone has a long half-life, therefore providing prolonged pain relief (28). Methadone, when used in conjunction with gabapentin, improves pain control and several QoL/function metrics (20,29). While it is unclear whether high dose gabapentin adds additional benefit to methadone, we recommend the use of methadone for pain relief in patients not well controlled on high dose gabapentin and over-counter-analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial found that methadone gave better and faster relief of cancer pain with a neuropathic component, compared with fentanyl. 15,16 Reddy et al 17 found no significant difference in overall survival among cancer patients taking methadone compared with other opioids, whereas a systematic review suggested switching from morphine/oxycodone to methadone as 1 of 3 weak recommendations for the management of opioid-induced nausea and vomiting. 18 A comparative retrospective study showed that early switching to methadone may be useful for control of advanced cancer pain.…”
Section: Discussionmentioning
confidence: 99%